2007
DOI: 10.1055/s-2007-966780
|View full text |Cite
|
Sign up to set email alerts
|

Heads or tails, does it make a difference? Capsule endoscope direction in small bowel studies is important

Abstract: Capsule endoscopy has opened the small bowel for direct inspection. However, the diagnostic sensitivity of capsule endoscopy is not 100 %. We have observed that forward orientation and backward orientation of the camera in the small bowel provide different information on pathological findings. Double-head capsule endoscopy may offer the answer to this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
5
1
Order By: Relevance
“…Our prospective study compares the performance of SB3 and PillCam Colon 2 capsules for the investigation of suspected small bowel bleeding. Previous studies of pan-intestinal capsule investigation and double headed small bowel capsules have suggested a bidirectional, double headed, capsule, including PillCam Colon 2, designed for colonic imaging, may have a diagnostic advantage in the small bowel (6,7,13,14). Our findings do not support this hypothesis.…”
Section: Discussioncontrasting
confidence: 89%
“…Our prospective study compares the performance of SB3 and PillCam Colon 2 capsules for the investigation of suspected small bowel bleeding. Previous studies of pan-intestinal capsule investigation and double headed small bowel capsules have suggested a bidirectional, double headed, capsule, including PillCam Colon 2, designed for colonic imaging, may have a diagnostic advantage in the small bowel (6,7,13,14). Our findings do not support this hypothesis.…”
Section: Discussioncontrasting
confidence: 89%
“…The exact contribution of this factor is uncertain; however, it is clear that some of findings may escape the camera that is facing the opposite direction despite it's wide angle of capture (for example, 156°for PillCam TM SB2 and 140°for PillCam TM SB1). In a study by Adler and Metzger [3], three patients with Crohn's disease underwent two capsule endoscopies each within a week. The capsule traversed the pylorus in opposite direction in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…The direction of the passage of the ileocecal valve was determined as head first when a clear view of the valve with a following appearance of a cecal image was obtained. If no image of the ileocecal valve was obtained, the direction of the passage was described as tail-first [3].…”
Section: Determination Of Movement Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Kopylov et al point out, previous data suggest that that the vector of CE small-bowel transit impacts on the CE diagnostic yield [2]. It has been shown that single-headed CE may have limitations when compared to double-headed CE [3,4], in the detection of anatomical landmarks, i.e., ampulla of Vater.…”
mentioning
confidence: 99%